2009
DOI: 10.1016/j.pbb.2009.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation of the nucleus accumbens reduces ethanol consumption in rats

Abstract: Recent studies have shown that deep brain stimulation (DBS) of the nucleus accumbens (NAcc) has an inhibitory effect on drug-seeking behaviors including reinstatement responding for cocaine. The objective of the present study was to expand on these findings by assessing the effects of DBS on behaviors related to alcohol consumption. The specific aim of this study was to determine whether DBS delivered to either the shell or core of the NAcc would reduce ETOH intake in rats using a twobottle choice limited acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 40 publications
(46 reference statements)
9
78
2
1
Order By: Relevance
“…Using a similar viral transfer system, overexpression of 5-HT1B receptors in the nucleus accumbens was shown to enhance ethanol consumption in rats trained to consume ethanol (Hoplight et al, 2006). Maintenance of ethanol self-administration is reduced among others after the pharmacological blockade of mGluR5 receptors in the nucleus accumbens, but not the dorsomedial striatum or prefrontal cortex (Besheer et al, 2010) and deep brain stimulation of the nucleus accumbens shell and core (Knapp et al, 2009). Further, the nucleus accumbens also contributes to increased alcohol seeking that is observed during abstinence, i.e., incubation of alcohol seeking.…”
Section: Alcoholmentioning
confidence: 99%
“…Using a similar viral transfer system, overexpression of 5-HT1B receptors in the nucleus accumbens was shown to enhance ethanol consumption in rats trained to consume ethanol (Hoplight et al, 2006). Maintenance of ethanol self-administration is reduced among others after the pharmacological blockade of mGluR5 receptors in the nucleus accumbens, but not the dorsomedial striatum or prefrontal cortex (Besheer et al, 2010) and deep brain stimulation of the nucleus accumbens shell and core (Knapp et al, 2009). Further, the nucleus accumbens also contributes to increased alcohol seeking that is observed during abstinence, i.e., incubation of alcohol seeking.…”
Section: Alcoholmentioning
confidence: 99%
“…100 Several preclinical studies in rats have investigated the effect of high-frequency DBS on ethanol consumption and cocaine/narcotic-seeking behavior. 15,79,92,165,193 These studies showed a significant reduction in drugseeking behaviors following DBS.…”
Section: Addictionmentioning
confidence: 95%
“…Chez le rat, la stimulation profonde du NAc (core ou shell) peut réduire la consommation d'alcool [19]. La stimulation profonde de la partie dorsomédiane (shell), comme son inactivation pharmacologique, réduisent également la préférence et la consommation d'alcool [20,21].…”
Section: La Stimulation Profonde Du Noyau Accumbensunclassified